Electrochemical Sensor Based on Multi‐walled Carbon Nanotube/Gold Nanoparticle Modified Glassy Carbon Electrode for Detection of Estradiol in Environmental Samples. Issue 10 (12th June 2019) - Masikini, Milua; Ghica, Mariana Emilia; Baker, Priscilla G. L.; Iwuoha, Emmanuel I.; Brett, Christopher M. A.
Abstract: We report a rapid and simple method for sensing estradiol by electro‐oxidation on a multi‐walled carbon nanotube (MWCNT) and gold nanoparticle (AuNP) modified glassy carbon electrode (GCE). Compared with a bare GCE, AuNP/GCE and MWCNT/GCE, the composite modified GCE shows an enhanced response to estradiol in 0.1 M phosphate buffer solution. Experimental parameters, including pH and accumulation time for estradiol determination were optimised at AuNP/MWCNT/GCE. A pH of 7.0 was found to be optimum pH with an accumulation time of 5 minutes. Estradiol was determined by linear sweep voltammetry over a dynamic range up to 20 %mol L −1 and the limit of detection was estimated to be 7.0×10 −8  mol L −1 . The sensor was successfully applied to estradiol determination in tap water and waste water. Abstract :